Transformation of Digital Media Technology through Innovative Management: A New Perspective of Vocational High Schools in Industrial Revolution 4.0 - Arum Dwi Hastutiningsih; Nuryadin Eko Raharjo; Bryan Cabreros (Universitas Negeri Yogyakarta, 2024)
Background: The Industrial Revolution 4.0 has introduced significant challenges and opportunities for digital transformation in education, particularly in Vocational High Schools (VHS) in the Special Region of Yogyakarta (DIY). This transformation requires innovative management practices to integrate technology effectively into vocational education while addressing professional development and resource allocation challenges.Methods: This study employed a mixed-methods approach, collecting data from 34 VHS teachers in DIY. The data were analyzed to identify key factors influencing the success of digital transformation, including leadership vision, resource allocation, professional development, teacher collaboration, and regular evaluations.Results: The findings indicate that a clear leadership vision significantly supports technology integration in vocational education, bolstered by adequate resource allocation and regular training programs. Teacher collaboration emerged as a critical factor for successful technology adoption, although areas such as professional development and training enhancement were identified as needing improvement. Leadership support and periodic evaluations were also recognized as essential for sustaining progress.Conclusion: Strengthening professional development programs, fostering teacher collaboration, and optimizing leadership support are crucial to achieving effective digital transformation in Vocational High Schools in DIY during the Industrial Revolution 4.0 era.